Home Visiting and Outcomes of Preterm Infants: A Systematic Review - Goyal, Neera K. (American Academy of Pediatrics, 2013)
BACKGROUND AND OBJECTIVES: Home visiting is 1 strategy to improve child health and parenting. Since implementation of home visiting trials 2 decades ago, US preterm births (<37 weeks) have risen by 20%. The objective of this study was to review evidence regarding home visiting and outcomes of preterm infants METHODS: Searches of Medline, Cumulative Index to Nursing and Allied Health Literature, Cochrane Database of Systematic Reviews, Cochrane Controlled Trial Register, PsycINFO, and Embase were conducted. Criteria for inclusion were (1) cohort or controlled trial designs; (2) home-based, preventive services for infants at medical or social risk; and (3) outcomes reported for infants born preterm or low birth weight (<2500 g). Data from eligible reports were abstracted by 2 reviewers. Random effects meta-analysis was used to synthesize data for developmental and parent interaction measures. RESULTS: Seventeen studies (15 controlled trials, 2 cohort studies) were reviewed. Five outcome domains were identified: infant development, parent-infant interaction, morbidity, abuse/neglect, and growth/nutrition. Six studies (n = 336) demonstrated a pooled standardized mean difference of 0.79 (95% confidence interval 0.57 to 1.02) in Home Observation for Measurement of the Environment Inventory scores at 1 year in the home-visited groups versus control. Evidence for other outcomes was limited. Methodological limitations were common. CONCLUSIONS: Reviewed studies suggest that home visiting for preterm infants promotes improved parent-infant interaction. Further study of interventions targeting preterm infants within existing programs may strengthen the impact and cost benefits of home visiting in at-risk populations.